Keterampilan Intelektual Warganegara: Studi Pada Peserta Didik SMKN 2 Tulung Agung - Rochmadi, Nur Wahyu; Efendi, Yuherni; Rochastuti, Laras Ati (University of Muhammadiyah Malang, 2024)
Human resource competency demands must have the ability to think critically, laterally and systemically, especially in the context of problem solving (critical-thinking and problem-solving skills). These competencies are in line with the intellectual skills capabilities as learning outcomes proposed by Gagne. Starting from this, research was carried out in the form of identifying the intellectual skills of citizens regarding the basis of the Indonesian state of Pancasila among students of SMKN 2 Tulung Agung. The aim research is to identify students' intellectual skills as Indonesian citizens. The research was conducted with a quantitative descriptive design. The focus is intellectual skills towards the foundation of the Indonesian state, Pancasila. The research instrument used was a test. Data were analyzed using descriptive statistics. Research findings show that the intellectual skills of students at SMKN 2 Tulung Agung are in the medium category, with an average score of 70.897. The average intellectual skills score in the discrimination category was 75.329 (medium); the abstract concept category was 66,073 (medium); concrete concept category of 76.9878 (medium); rule category of 83.7439 (high); and the problems solving category was 52.3536 (low). Based on research findings, it is recommended to develop learning that focuses on increasing students' intellectual skills capabilities systematically, completely and continuously.